Sosialisasi Strategi Digital Marketing pada UMKM di Desa Gisting Bawah : Studi Kasus Keripik Pisang Anggun - Eny Inti Suryani; Nining Apriani; Salma Mahfuz; Reina Tri Deswita; Yuva Monica Sari; Sururuzaman Sururuzaman; Raden Indigo Zulto; Salman Lintang Firdaus; David Ardiyansyah; Rizky Kurniawan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study examines how micro, small and medium enterprises (MSMEs) in Gisting Bawah Village, Tanggamus Regency, Lampung Province, use digital marketing strategies. The focus of the study is Anggun banana chips. The purpose of this study is to examine current digital marketing practices, identify problems and opportunities, and find ways to increase sales and expand market reach. Using an observation and interview approach, this study found that, although Anggun banana chips have growth potential due to their high-quality products and organized production processes, the company faces difficulties in creating consistent content and creating effective promotional strategies on the internet. This part of the study provides MSME owners with practical knowledge on how to create engaging content, optimize the use of social media, and use successful digital marketing strategies. This study shows that MSMEs such as Anggun banana chips can significantly increase their market visibility, strengthen customer relationships, and potentially increase their revenues by using the right digital marketing techniques. This study will add to the body of research on rural MSMEs using digital marketing and offer practical insights for similar businesses looking to improve their brand's digital presence.